Learn to code HTML & CSS : develop & style websites - Howe, Shay (New Riders, 2014)
HTML and CSS can be a little daunting at first but fear not. This book, based on Shay Howe's popular workshop covers the basics and breaks down the barrier to entry, showing readers how they can start using HTML and CSS through practical techniques today. They'll find accompanying code examples online, while they explore topics such as the different structures of HTML and CSS, and common terms. After establishing a basic understanding of HTML and CSS a deeper dive is taken into the box model and how to work with floats. The book includes an exercise focused on cleaning up a web page by improving the user interface and design, solely using HTML and CSS. With a few quick changes the web page changes shape and comes to life. Interactive, technically up-to-the-minute and easy-to-understand, this book will advance a student's skills to a professional level.